"ONLY THE HUMAN WAY MAY BE FOLLOWED" READING THE GUODIAN MANUSCRIPTS AGAINST THE MOZI. (26th June 2014) - Meyer, Andrew
Abstract: Though the Guodian manuscripts have been viewed as an eclectic mix of texts, this article argues that, viewed in historical context, the collection has more coherence than has conventionally been supposed. Since the texts were interred in Chu c. 300 b.c.e., they should be read against other expressions of that time and place. The Mozi, much of which was likely used or produced by authors active in Chu at the time of the Guodian internment, is particularly illuminating in this regard. Though the individual Guodian texts do frequently contradict one another, they are yet commonly useful for formulating logical and rhetorical attacks on the teachings of the Mozi . The occupant of Guodian Tomb Number One may thus have collected these texts not for their doctrinal consistency with one another, but for their usefulness in use against intellectual opponents (among whom the Mohists clearly ranked). This, in fact, was likely a guiding principle for many Warring States literati in negotiating their production and utilization of texts. 摘要: 虽然郭店楚简的几篇文章被认为杂乱混合，其实它们的采集比较有道理。即使简文于公元前 300 年左右在楚国被埋葬，我们应该把它们和同时同地的文章比起来。做为这种比较，墨子 特别有用。虽然郭店简文互相有矛盾，可是它们都一样对反抗墨子的教导有用。郭店第一墓的墓主，采集文章的时候，大概是选择能用反对知识对手的材料，不管它们之间有没有冲突。这果然是战国时代文士创作与应用文章的基本原则。